2016
DOI: 10.3109/13880209.2015.1104702
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-inflammatory activity and standardisation of hydro-methanol extract of underground tuber ofDioscorea alata

Abstract: Context The underground edible tuber of Dioscorea alata L. (Dioscoreaceae) is a functional food with high nutritive value and therapeutic potential. The tuber is known to possess antiinflammatory properties in traditional medicine. Objective The present study explores the anti-inflammatory activity and standardisation of D. alata tuber hydromethanol extract. Materials and methods Hydromethanol extract (70%) of D. alata tuber was chemically characterised using HPLC and GC-MS techniques. Murine lymphocytes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Although recent studies have highlighted the anti-inflammatory effect of Dioscorea spp., the mechanism underlying the protective effect against ethanol-induced damage is incompletely understood [ 26 , 27 , 28 ]. We examined the anti-inflammatory activity of DBD extracts in acute gastric ulcer in mice by evaluating the plasma levels of NO, IL-6, and TNFα ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies have highlighted the anti-inflammatory effect of Dioscorea spp., the mechanism underlying the protective effect against ethanol-induced damage is incompletely understood [ 26 , 27 , 28 ]. We examined the anti-inflammatory activity of DBD extracts in acute gastric ulcer in mice by evaluating the plasma levels of NO, IL-6, and TNFα ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dioscorea species, belonging to the family Dioscoreaceae, are mostly grown for their starchy tubers or medicinal properties [ 26 , 28 , 30 ]. DBD is known to have biologically beneficial effects including antioxidative, antidiabetic, anti-atherosclerotic, and anti-inflammatory activities [ 14 , 16 , 17 , 27 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed effect of yam powder was attributed to its potential to lower inflammatory cytokines as well as scavenging free radicals and up-regulating activity of carbonic anhydrase. The hydro-methanol extract of D. alata tubers which contain different bioactive phytocompound has also shown to significantly down-regulate the pro-inflammatory signals in a gradual manner compared to a reference control (µg/mL) [ 203 ]. Mollica et al [ 273 ] reported the anti-inflammatory activity of extract from D. trifida on food allergy induced by ovalbumin in mice.…”
Section: Therapeutic Potentials Of Yamsmentioning
confidence: 99%
“…Regarding the other Dioscorea species, D. alata tuber extract has been reported to possess a potent anti-inflammatory effect by inhibition of the NO and TNF-α expression [23]. D. batatas peel extract decreased NO production and proinflammatory protein expression and decreased the level of ROS [24].…”
Section: Plos Onementioning
confidence: 99%